Biochemistry and molecular biology - Sheehan, Moria (Thomas Nelson & sons, 1994)
Each book contains clear chapter objectives and closing summaries, a range of independent learning activities including assignments, analysis exercises and in-text questions. Science is presented in context with strong emphasis on economic, social and environmental factors.